THE THE RELATIONSHIP BETWEEN BREAST CANCER EARLY DETECTION MOTIVATION AND “SADARI” PRACTICE TOWARDS MEDICAL STUDENTS OF STIKES MAHARANI: HUBUNGAN ANTARA MOTIVASI DETEKSI DINI KANKER PAYUDARA DENGAN PRAKTIK SADARI MAHASISWI STIKes MAHARANI - Diana Noor Fatmawati; Evi Dwi Prasitiwi (Poltekkes Kemenkes Malang, 2021)
Late diagnosis of breast cancer generally occurs because it is not detected at an early stage. The safest way to deal with cancer is detect it as soon as possible before it develops become more severe. Therefore, it is very important to have regular check-ups on a regular basis as an effort to prevent and detect breast cancer earlier. Breast self-examination or periksa payudara sendiri (SADARI) is one of the early detection self-procedure to prevent breast cancer. This procedure will be more effective if done as early as possible starting when women already reach their reproductive age. Objective: This research aimed to find out the relationship between motivation about breast cancer early detection and “Sadari practice. Methods: This research was correlational non-experimental with crosssectional approach. The sampling technique used is simple random sampling with a research sample of 77 students from STIKes Maharani. Collected data were analyzed using Spearman Rho. Results: 55 (71.4%) female students who have high motivation for early detection of breast cancer practice “Sadari” and 14 (18.2%) female students who have low motivation for early detection of breast cancer do not practice “Sadari”. Spearman Rho test result showed that p value is 0.001 (p less than 0.01) and in this case, mean the Ho is rejected and Ha is accepted. This result suggested that there is a relationship between motivation for early detection of breast cancer and “SADARI” practice. Conclusions and Suggestions: The female students should be able to be more routine in doing ”SADARI” practice. Keywords: Motivation, Mindfulness Practice, Early Detection of Breast Cancer